Pattern of Professional Development of Human Resources of Knowledge-based Companies(Study case: Science and Technology Park of Iranian Research Organization for Science and Technology) - Bijan Abdollahi; Jafar Salemi; hasan zeinabadi; ghasem Ramezanpour nargesi (پژوهش‌های مدیریت عمومی)
AbstractThe role of knowledge-oriented human resources in knowledge-based companies is very prominent as one of the main characteristics (and indeed capital) of these companies that affect their success; Therefore, this research was conducted with the aim of designing a Pattern for the development of human resources of knowledge-based companies in the Science and Technology Park of the Scientific and Industrial Research Organization of Iran.This qualitative study was a content analysis type. The research community included organizational experts and organizational managers with knowledge of human resources, of which 15 experts were selected using the purposeful sampling method and in the form of a snowball. Data analysis was done by content analysis method with inductive approach and coding. By coding the extracted interviews, 442 initial concepts, 149 indicators, 23 dimensions and 4 components were identified, of which the four main components were planning and policy making, teaching and learning, implementation and design and performance management To increase the internal validity of the study, member checking method was used. The findings of this study help stakeholders, policy makers and management of small and medium companies to benefit from appropriate human resource development methods to improve employee competencies and increase organizational effectiveness.IntroductionThe term "knowledge-based companies" or similar words is considered a relatively new term in the world's management and economic literature, so that many countries have not yet provided a precise and clear definition of it (Gorman, & McCarthy, 2006; Aliabadi et al., 2019). Regarding what a startup is, there is no consensus among the activists and researchers in the field of new businesses. Knowledge-based companies have a special role and importance in economic progress and national development. For growth and excellence, the factors affecting it must be identified and managed (Hult et al, 2004) and if these factors are not known, the nature of the process will be damaged and the resources, efforts, time and money that have been spent will be wasted (Park et al). , 2019). Another important point in these definitions is that start-up is usually the result of group activity and not an individual activity. Regullary; A startup consists of a number of co-founders who are responsible for the idea and main activity of the startup and are in charge of its executive and technical affairs (Oliveira, 2019). Regarding the importance of designing a model for the professional development of human resources in knowledge-based companies, it should be mentioned that the trustees and human forces active in these centers, despite their scientific capabilities, do not have the necessary skills to carry out businesses to the stage of commercialization and profitability, and may have many plans. important and income-generating does not reach the stage of exploitation due to the lack of human resources; Therefore, this research seeks to answer the main question, what is the pattern of professional development of human resources in knowledge-based companies?Case studiesThe current research, which was carried out under the title of "designing a policy model for the development of human resources of knowledge-based companies in the Science and Technology Park of the Scientific and Industrial Research Organization of Iran"Materials and MethodsThe current research, which was carried out under the title of "designing the policy model of human resources development of knowledge-based companies in Science and Technology Park of the Scientific and Industrial Research Organization of Iran", is in the category of applied research. This research was one of the exploratory researches and used the strategy of content analysis. In the qualitative part, the relevant categories were first extracted using library studies and semi-structured interviews, and the categories were converted into models using qualitative methods such as content analysis; Therefore, it can be said that the research method in this study was qualitative; in which interviews and documents were analyzed using the content analysis method. The experts of the qualitative department were divided into two groups in this research; In the first part, there were experts from the Scientific and Industrial Research Organization of Iran, who had more than 5 years of work experience in knowledge-based companies, and in the second part, the experts included managers of knowledge-based companies located in Science and Technology Park. There were 12 participants in this research. Sampling method In the qualitative part of the research, the purposeful and theoretical sampling method was used, which was carried out to the extent of sufficiency and theoretical saturation of the interviews. The main tool used in this research is semi-structured interviews. After each interview, based on theoretical snowball sampling, the interviewees were asked to introduce people who they think are good experts on the subject.Discussion and resultsIn this research, in order to collect data using the purposeful sampling method, 12 subject matter experts and experts from knowledge-based companies who were related to the policy issues of human resource development of knowledge-based companies were selected. The current research was conducted with the aim of abstracting different aspects of the human resource development policy model of knowledge-based companies in the Science and Technology Park of the Scientific and Industrial Research Organization of Iran. By studying the extracted data and information, 442 primary concepts, 149 indicators, 23 dimensions and 4 components were identified.ConclusionThis research has also provided a model that can be used as a conceptual framework for the study of human resources development policies of knowledge-based companies and policies to operationalize the developed model. However, there is one thing that is often overlooked by many knowledge-based company founders and that is the power of employee development. Employee development is the key to unlocking the team's full potential and driving business growth. This foundation of knowledge-based company culture is strong and sustainable and can make a difference in business success. Employers who invest in employee development help their employees build on their strengths and develop skills that better equip them for their current roles. This adds value to what they do and directly benefits the business.